The impact of different agroecological conditions on the nutritional composition of quinoa seeds - María Reguera; Carlos Manuel Conesa; Alejandro Gil-Gómez; Claudia Mónika Haros; Miguel Ángel Pérez-Casas; Vilbett Briones-Labarca; Luis Bolaños; Ildefonso Bonilla; Rodrigo Álvarez; Katherine Pinto; Ángel Mujica; Luisa Bascuñán-Godoy (PeerJ, 2018)
Quinoa cultivation has been expanded around the world in the last decade and is considered an exceptional crop with the potential of contributing to food security worldwide. The exceptional nutritional value of quinoa seeds relies on their high protein content, their amino acid profile that includes a good balance of essential amino acids, the mineral composition and the presence of antioxidants and other important nutrients such as fiber or vitamins. Although several studies have pointed to the influence of different environmental stresses in certain nutritional components little attention has been paid to the effect of the agroecological context on the nutritional properties of the seeds what may strongly impact on the consumer food’s quality. Thus, aiming to evaluate the effect of the agroecological conditions on the nutritional profile of quinoa seeds we analyzed three quinoa cultivars (Salcedo-INIA, Titicaca and Regalona) at different locations (Spain, Peru and Chile). The results revealed that several nutritional parameters such as the amino acid profile, the protein content, the mineral composition and the phytate amount in the seeds depend on the location and cultivar while other parameters such as saponin or fiber were more stable across locations. Our results support the notion that nutritional characteristics of seeds may be determined by seed’s origin and further analysis are needed to define the exact mechanisms that control the changes in the seeds nutritional properties.